SOSIALISASI PENERAPAN PEMBUKUAN SEDERHANA BERBASIS AKUNTANSI PADA TOKO SEMBAKO BAPAK MUHAYAR KECAMATAN CIPAYUNG: Socialization of the Implementation of Simple Accounting-Based Bookbook at the Mr. Muhayar Grocery Store, Cipayung District - Sari , Asih Mutiara; Hermawan, Casandra; Matjik, Achmad Fatur Nurfauizi; Amelia, Suci; Permatasari, Yunita Indah; Djunaidy, Djunaidy (PUAN INDONESIA, 2024)
Micro, Small and Medium Enterprises or commonly called MSMEs are on the rise and are one of the government programs, which is stated in the Job Creation Law No. 20 of 2008. Bojong Village, Pondok Terong is one of the many other villages in Indonesia where the majority of the population are MSME actors. One of them is Mr. Muhayar who carries out MSME activities by opening a Basic Food Shop at his home. However, behind the rise of MSME activities, there are limited knowledge and insights related to managerial in the preparation of financial statements faced by grocery store owners. Therefore, this study aims to explore the socialization process and the application of simple accounting-based bookkeeping where this research involves active participation and interviews of MSME actors, namely in Mr. Muhayar's basic food shop business. This is done to increase understanding of the importance of good financial records, as well as to understand how accounting implementation can improve the efficiency and sustainability of micro-enterprises. The results of this study show that this socialization can make a positive contribution to the financial management of MSME actors. In addition, the results show that the application of simple bookkeeping provides a better understanding of cash flow, stock of goods, and profitability.